PENERAPAN SANKSI ADMINISTRATIF KEPADA NOTARIS OLEH MAJELIS PENGAWAS WILAYAH (MPW) MENURUT UNDANG UNDANG NOMOR 2 TAHUN 2014 TENTANG PERUBAHAN UNDANG UNDANG NOMOR 30 TAHUN 2004 TENTANG JABATAN NOTARIS - Muhammad Hafiz Tafdhil (Universitas Sriwijaya, 2015)
ABSTRACT: Notary is running his occupation there is conducted collision because the collision of Notary can be fallen by sanction. One of sanction to Notary is fallout of administrative sanction. Administrative sanction fallout to notary represent duty notary supervisor ceremony. One of them is the Regional Supervisor Ceremony (MPW), sanction fallout to notary so that the notary don’t act improperly and remain to obey order. Regional Supervisor Ceremony (MPW0 becoming problem here is how sanction fallout to notary conducting collision of pursuant to number law 2 years 2014 about notary. To reply this problem is hence conducted by a research conducted by Yuridis normative. Process administrative sanction fallout, what is the form of sanction and exhortation written, and also the layoff is regional duty Regional Supervisor Cerremony (MPW). On the basis of above conclusion, suggested that by of clear order existence about sanction fallout to notary conducting collision. Keyword : Notary, Regional Supervisor Ceremony (MPW), Sanction